EXCHANGE MARKET PRESSURE PENDETEKSI KRISIS KEUANGAN DI INDONESIA - Khairul Azhar; Hasdi Aimon; Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aimed to analyze: (1) Probability of Real Effective Exchange Rate, Foreign Exchange Reserves, Export, Import, loan to deposit ratio, Return to the assets of the financial crisis in Indonesia. Using data from the years 1995 to 2014 times series. This research is using Early warning system using econometric approach, through the Exchange Market Pressure (EMP). These results indicate: (1) Real Exchange Rate Efecctive have significant opportunities to the financial crisis. (2) The foreign exchange reserves have significant opportunities to the financial crisis. (3) Exports have significant opportunities to the financial crisis. (4) imports did not have significant opportunities to financial krissi. (5) The loan to deposit ratio has a significant opportunity to the financial crisis. (6) Return to Asset does not have significant opportunities to the financial crisis. (7) Real Efecctive Exchange Rate, foreign exchange reserves, exports, imports, loan to deposit ratio and Return to Asset jointly chance against the financial crisis in Indonesia.Keyword  : Exchange Market Pressure, Early Waring System crises